The effect of TiO2 surface on the electron injection efficiency in PbS quantum dot solar cells: a first-principles study1. Issue 8 (28th February 2015) - Azpiroz, Jon M.; Ugalde, Jesus M.; Etgar, Lioz; Infante, Ivan; De Angelis, Filippo
<x xml:space="preserve">Abstract</x> We present a density functional theory (DFT) study aimed at understanding the injection and recombination processes that occur at the interface between PbS Quantum Dots and different TiO2 surfaces.